Characteristics of Synbiotic Drink from Jicama (Pachyrhizus erosus L.) Tubers and Sunflower (Helianthus annuus L.) Seeds Extract - Winarti, Sri; Jariyah; Yusuf, Aulia Islamiati; Arum, Ardilini Destyaning (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
Synbiotic drinks are fermented beverages composed of ingredients that encompass prebiotics and probiotic bacteria. A study was conducted to develop a synbiotic drink using Jicama tubers extract and sunflower seeds extract along with the probiotic bacteria including Lactobacillus casei FNCC-0090, Lactobacillus acidophilus FNCC-0051, Bifidobacterium breve BRL-131, and Bifidobacterium bifidum BRL-130. The objective of this research was to assess the impact of varying proportions of Jicama tubers extract (Jc) and Sunflower seeds extract (Sf), as well as fermentation duration on the characteristics of synbiotic drinks. The experimental design employed a factorial completely randomized design with two factors: the proportions of Jicama and sunflower seed extract (75:25, 50:50, and 25:75) and fermentation time (8, 12, 16, and 20 h). Data from the study were analyzed using ANOVA (P<0.05), and significant differences between treatments were assessed by DMRT. The optimal treatment was determined at the 50:50 proportion of Jicama and sunflower seed extract, with an 20 h fermentation time, yielding a synbiotic drink characterized by total LAB of 11.34 log CFU/mL, total lactic acid of 1.29%, N-amino of 4.67 %, antioxidant activity of 33.5%, viscosity of 37.08 cP, inulin content of 1.03%, and vitamin E content of 0.58%.